2005
DOI: 10.1124/jpet.104.082768
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity of Nociceptin/Orphanin FQ Peptide Receptor Partial Agonists on Cardiovascular and Renal Function

Abstract: The opioid-like peptide nociceptin/orphanin FQ (N/OFQ) produces marked cardiovascular and renal responses after central or peripheral administration in rats. Due to their ability to behave as full/partial agonists or antagonists in different cellular and tissue assays, the present studies were performed to determine how compounds classified as N/OFQ peptide (NOP) receptor partial agonists ([F/G]N/OFQ(1-13)-NH 2 , Ac-RYYRIK-NH 2 , and Ac-RYYRWK-NH 2 ) affect cardiovascular and renal function in vivo. In conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Ac-RYYRWK-NH 2 was chosen as the parent compound based on the results of investigations in which we demonstrated that the NOP receptor partial agonist Ac-RYYRWK-NH 2 produced a modest water diuresis after i.v. bolus injection in conscious rats (Kapusta et al, 2005). In addition to this compound's agonist-like effects on kidney function, we also showed that Ac-RYYRWK-NH 2 (and other ligands historically classified as NOP receptor partial agonists; Calo' et al, 2000) behaved as a weak partial agonist, eliciting a slight reduction in mean arterial pressure without affecting heart rate.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Ac-RYYRWK-NH 2 was chosen as the parent compound based on the results of investigations in which we demonstrated that the NOP receptor partial agonist Ac-RYYRWK-NH 2 produced a modest water diuresis after i.v. bolus injection in conscious rats (Kapusta et al, 2005). In addition to this compound's agonist-like effects on kidney function, we also showed that Ac-RYYRWK-NH 2 (and other ligands historically classified as NOP receptor partial agonists; Calo' et al, 2000) behaved as a weak partial agonist, eliciting a slight reduction in mean arterial pressure without affecting heart rate.…”
mentioning
confidence: 75%
“…However, the enzymatic instability of endogenous N/OFQ makes this peptide unsuitable for clinical use. To circumvent this problem, we developed a novel NOP receptor ligand that was created by applying the structure-inducing probe (SIP) technology (Larsen and Holm, 1998;Larsen, 1999;Larsen et al, 2001;Kapusta et al, 2002) to the compound Ac-RYYRWK-NH 2 , a purported NOP receptor partial agonist (Dooley et al, 1997;Kapusta et al, 2005). The principle of the SIP technology is that a short (5-10-amino acid) sequence of certain charged amino acids (e.g., lysine or asparagine) forms an ␣-helical structure, which when attached to the C or N terminus of another peptide may twist the whole peptide into an ␣-helix and prevent enzymatic degradation (Larsen et al, 2001;Larsen, 2003).…”
mentioning
confidence: 99%
“…In addition to increased potency, UFP-112 also produced markedly longer cardiovascular responses than N/OFQ. In this regard, the changes in mean arterial pressure and heart rate produced by N/OFQ at 10 nmol/kg (present study; figures 7 and 8) or higher (30 and 100 nmol/kg; [33]) recovered within 10-min post-drug injection. At the 10 nmol/ kg dose UFP-112 significantly decreased heart rate and mean arterial pressure throughout the 80-min protocol (figure 8).…”
Section: Cardiovascular and Renal Responses In Ratsmentioning
confidence: 86%
“…These responses to UFP-112 are different to those to the natural ligand N/OFQ, which at all previously tested doses up to 1000 nmol/kg i.v. bolus has not produced diuresis ( [33] and Kapusta et al, unpublished results). There are two possible explanations for the ability of UFP-112 to produce a diuretic response after bolus injection i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation